Analysing Properties of Asphalt Concrete Modified with Crumb Rubber Compare to Other Mixture - Abdallh. A. A. Lhwaint; Mohmed Alshekh A. M. Hmade; Ervina Ahyudanari; Indrasurya B. Mochtar; Abrahem A Ali blash (IPTEK Journal of Proceedings Series, 2017)
Several  researchers have been undertake in finding alternative materials in order to be used as a modifier in asphalt mixture for the purpose of improving its properties. This research presents a study of laboratory evaluation on the performance of hot-mixed asphalt (HMA) using crumb rubber as an additive. It is noted that crumb rubber was identified to have potency as a modifier in HMA due to the elastic behavior exposed by the rubber particles, especially in reducing the rutting potential. This study fine crumb rubber Shred (2.36-0.85 mm) obtained by ambient-temperature grinding process from discarded truck tires, was used to modify asphalt concert. The fine crumb rubber with different contents, i.e. 2.5%, 5%, 7.5% and 10%, was incorporated into the mixture by using dry and wet process method in differentent temperatures. The Marshal properties, Unconfined Compressive Strength (UCS), Indirect Tensile Strength test (ITS) and Indirect Tensile Strength Modulus (ITSM), Permeability   were conducted. The result showed that marshal stability, Marshal Quotient, Voids in Mix (VIM) and Voids in mineral aggregate (VMA) decreased with the increasing crumb rubber modifier. However, Marshal Flow and Void filled with asphalt (VFWA) increased when crumb rubber modifier was increased. The crumb rubber asphalt mixture result indicated has increased amount of crumb rubber in asphalt concrete mixture will decrease the Marshall Stability and permeability test shows that asphalt concrete without crumb rubber lower than AC with crumb rubber strength compare to other mixture.